An Analysis of The Role of Law In The Formation of Social Identity In Urban Communities - Abimanyu Rizki Ardila Putra; Rohmat Sudrajat; Mohamad Iqbal Saputra; Sigit Gunawan; Deni Yusup Permana (Pelopor Publikasi Akademika, 2024)
Urban society is a complex and dynamic society, with various social identities that are formed and developed. In the midst of this complexity, law plays an important role in shaping and influencing the social identity of individuals and groups in urban society. This research aims to analyze the role of law in the formation of social identity in urban communities. This research uses a non-doctrinal research method. The data collection technique in this research is a literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and conclusion drawing. The results showed that law has a complex and multidimensional role in the formation of social identity in urban communities. Law can act as a framework that regulates social interaction and maintains public order. Effective law enforcement contributes to creating a sense of justice and equality among urban citizens. It strengthens the social identity of individuals and groups by providing them with a sense of security and protection under the umbrella of the law. In addition, the law also influences the way individuals and groups interact with each other, shaping social norms that become an integral part of the social identity of urban communities.